MUSIC AND SPACE - MURARIU, Alexandru-Ștefan (Studia Universitatis Babes-Bolyai Musica, 2017)
The present study proposes an insight of the use of space by composers worldwide during several centuries. From the first appearances dated in the Renaissance period until our days, space has been used in a many ways and this aspect inspired composers from all the important periods of time. From Giovanni Gabrieli to Beethoven or Mozart, from Mahler to Henry Brant or Kurtág, each composer exploited space in many ways in order to harness their visions on both programmatic and concrete music. In our days, a very important role in the development process of spatialized music is given to the electro-acoustic trend which expanded in many ways throughout the important studios in Europe and United States. Other important features in this field of music is the sound scaping trend. Numerous artists are looking to extract as much possible from a specific space by recording or exploiting its acoustics and aural architecture.